SLM2 is a novel cardiac splicing factor involved in heart failure due to dilated cardiomyopathy - Boeckel, Jes-Niels; Möbius-Winkler, Maximilian Nicolas Werner; Müller, Marion; Rebs, Sabine; Eger, Nicole; Schoppe, Laura; Tappu, Rewati; Kokot, Karoline E.; Kneuer, Jasmin Marga; Gaul, Susanne; Bordalo, Diana M.; Lai, Alan; et al. (Genomics, proteomics & bioinformatics, 2021)
Alternative mRNA splicing is a fundamental process to increase the versatility of the genome. In humans, cardiac mRNA splicing is involved in the pathophysiology of heart failure. Mutations in the splicing factor RNA binding motif protein 20 (RBM20) cause severe forms of cardiomyopathy. To identify novel cardiomyopathy-associated splicing factors, RNA-seq and tissue-enrichment analyses were performed, which identified up-regulated expression of Sam68-Like mammalian protein 2 (SLM2) in the left ventricle of dilated cardiomyopathy (DCM) patients. In the human heart, SLM2 binds to important transcripts of sarcomere constituents, such as those encoding myosin light chain 2 (MYL2), troponin I3 (TNNI3), troponin T2 (TNNT2), tropomyosin 1/2 (TPM1/2), and titin (TTN). Mechanistically, SLM2 mediates intron retention, prevents exon exclusion, and thereby mediates alternative splicing of the mRNA regions encoding the variable proline-, glutamate-, valine-, and lysine-rich (PEVK) domain and another part of the I-band region of titin. In summary, SLM2 is a novel cardiac splicing regulator with essential functions for maintaining cardiomyocyte integrity by binding to and processing the mRNAs of essential cardiac constituents such as titin.
Gesehen am 13.12.2022